Synthetic Thiol and Selenol Derived Amino Acids for Expanding the Scope of Chemical Protein Synthesis - Guan, Ivy; Williams, Kayla; Liu, Joanna Shu Ting; Liu, Xuyu (Frontiers in Chemistry, 2022)
Cells employ post-translational modifications (PTMs) as key mechanisms to expand proteome diversity beyond the inherent limitations of a concise genome. The ability to incorporate post-translationally modified amino acids into protein targets via chemical ligation of peptide fragments has enabled the access to homogeneous proteins bearing discrete PTM patterns and empowered functional elucidation of individual modification sites. Native chemical ligation (NCL) represents a powerful and robust means for convergent assembly of two homogeneous, unprotected peptides bearing an N-terminal cysteine residue and a C-terminal thioester, respectively. The subsequent discovery that protein cysteine residues can be chemoselectively desulfurized to alanine has ignited tremendous interest in preparing unnatural thiol-derived variants of proteogenic amino acids for chemical protein synthesis following the ligation-desulfurization logic. Recently, the 21st amino acid selenocysteine, together with other selenyl derivatives of amino acids, have been shown to facilitate ultrafast ligation with peptidyl selenoesters, while the advancement in deselenization chemistry has provided reliable bio-orthogonality to PTMs and other amino acids. The combination of these ligation techniques and desulfurization/deselenization chemistries has led to streamlined synthesis of multiple structurally-complex, post-translationally modified proteins. In this review, we aim to summarise the latest chemical synthesis of thiolated and selenylated amino-acid building blocks and exemplify their important roles in conquering challenging protein targets with distinct PTM patterns.